The importance of taking into account behavior irreversibilities when simulating the forming of textile composite reinforcements. (December 2019) - Abdul Ghafour, T.; Colmars, J.; Boisse, P.
Abstract: Simulations of the forming of textile composite reinforcements are generally based on elastic behavior models. However, the slippage between the fibers and the associated friction that occurs during shaping creates irreversibilities. The present paper describes the modeling and identification of these irreversibilities from bending and bias extension tests. In classic forming cases, simulations that either took into account or neglected the irreversibilities, were compared. The geometries of the reinforcements after forming generally did not show significant differences. On the other hand, the internal forces in the reinforcement were found to differ. In addition, the results of elastic and inelastic simulations were very different in the case of a punch removal. This shows that the behavior of a textile reinforcement during forming is inherently irreversible and should be described by an inelastic model in the general case. In the liquid infusion processes, elastic simulations can be considered because the punch is not removed.